2020
DOI: 10.21873/invivo.11822
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients With Metastatic Renal Cell Cancer and Bone Metastases

Abstract: Background/Aim: Previous research has ResultsBaseline characteristics. The majority of patients had clear cell histology (83%), male gender (77%), age between 60 and 69 years (74%), distant metastases at the time of initial 675 This article is freely accessible online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…and the high adherence to national guidelines in our institution and region (22,23), results are difficult to compare. In several of our own studies (4,5,(22)(23)(24), including the present one, we have so far not identified areas of concern regarding treatment access and efficacy in the framework of the publicly-funded healthcare system.…”
Section: Discussionmentioning
confidence: 82%
“…and the high adherence to national guidelines in our institution and region (22,23), results are difficult to compare. In several of our own studies (4,5,(22)(23)(24), including the present one, we have so far not identified areas of concern regarding treatment access and efficacy in the framework of the publicly-funded healthcare system.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, the OS for a vast majority of patients continues to be restricted. [98] Recent advancements in image-guided ablation technologies have shown considerable promise in managing pain associated with osseous metastases. [27] In the study by Gardner et al, minimally invasive cryoablation could represent a viable treatment alternative for approximately 75% of BOM-RCC patients who are not candidates for surgical resection.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%
“…The survival prognosis of these patients is heterogeneous, too. Pain might be present already as the first sign of cancer in patients expected to survive for several years, or in the pre-terminal and terminal phase when all systemic therapies have been stopped due to futility and/or the patients' reduced general condition (4)(5)(6)(7)(8). This heterogeneity causes uncertainty regarding treatment decisions, such as the decision to irradiate at all and the choice of fractionation regimen (9)(10)(11).…”
mentioning
confidence: 99%